Degree Days: Heating, Cooling, and Growing - Clyde W. Fraisse; John Bellow; Charles M. Brown (EDIS)
ABE-381, a 7-page illustrated fact sheet by Clyde W. Fraisse, John Bellow, and Charles Brown, discusses how growers can use the AgClimate Web site to find out how to predict Growing Degree Day accumulation for the current season, and to review GDD for past seasons. Includes references. Published by the UF Department of Agricultural and Biological Engineering, October 2007.